The Influence of Several Host Types on the Balance of Life Sitophilus Sp - Nik, Nikolas; Rusae, Aloysius (Jurnal Penelitian Pendidikan IPA, 2024)
Sitophilus sp is a warehouse pest that attacks grain. In its life cycle, Sitophilus sp requires hosts such as rice, corn and sorghum for its survival process. This warehouse pest can damage crops in the form of pods or seeds in the field or in storage. This research aims to determine the life cycle of Sitophilus sp on several different types of hosts. This research used a single factor Completely Randomized Design (CRD) consisting of six levels which were repeated 10 times. The results of the study showed that the fastest development of Sitophilus sp was in local white rice (35.00 days), and the longest development was in Lamuru corn (46.00 days). In the life balance table, local white corn produces the highest growth and development (proportion) of live Sitophilus sp. Meanwhile, the lowest live proportion is found in lamuru corn.